Сучасний стан логістичної системи в умовах пандемії COVID-19 - ZRYBNIEVA, Iryna (Міжнародна науково-практична конференція «Трансформація податкової та обліково- аналітичної систем в контексті сучасних кризових явищ», 2021)
Increased competition in market relations leads to the transformation of logistics systems through increasing the speed of material flow, increasing the intensity and complexity of the accompanying information flow, complicating financial relationships, reducing the number of links in the logistics chain, reducing its reliability. The consequence of these trends is an increase in the potential instability of logistics systems. Changing the growing problems and achieving the strategic goals of the business, the prospects for its development is possible only with further integration both within the logistics chain and externally, taking into account the dynamics of the external environment.
CURRENT STATE OF THE LOGISTICS SYSTEM IN THE COVID-19 PANDEMIC CONDITIONS
Keywords: logictics; logistics system